«The Journal of Ministry of Public Education» is an Important Source of Investigation of Private School Education Development - Svitlana Royenko (Pedagogical Discourse, 2013)
The article presents the attempt to consider the problem of covering the private school education development on pages of «The Journal of Ministry of Public Education» (1834-1917). Special attention is paid to studing the reports issued by Ministers of Public Education and guardians of educational districts. Their analysis  allowed to trace back the development of private school education during the observable period, and to find out the governmental policy concerning private institutions. Among the documents «The comparative statements about the condition of educational institutions of the Ministry of Public Education ...» and «The supplement to the nation-wide report of the Minister of Public Education» deserve special attention as they give an opportunity to trace the development dynamics of the network of educational establishments of different types on the basis of statistical statements. The published work «The issue on the state of our private educational institutions» which presents the situation in the sphere of private education during a long period of time  is  examined in the context of the research.